Assisted Dying and Suicide Prevention - Jones, David Albert 1966- (2018)
The author presents two examples of suicide by disabled people, one unassisted and one assisted. There are points of dissimilarity but also points of similarity. The language of "assisted dying" is misleading especially when the person is not terminally ill. In contrast, the language of "assisted suicide" is appropriate and is used in Switzerland and the Benelux countries. Guidance is needed for media reporting of assisted suicides. In addition to avoidance of certain details and ways of framing stories, the media should also seek to tell more positive stories about life with disability, counteracting the Werther effect with the Papageno effect. This article concerns suicide prevention in relation to the practice and the reporting of assisted dying. Its focus is the situation of people who are suicidal and who have a physical disability or a mental health condition. The aim of the article is not to consider the current or possible future shape of the law in different jurisdictions in relation to determining, assisting and encouraging, or preventing suicide. It aims, rather, to call attention to danger of suicide, whether assisted or unassisted, among people who would be eligible for euthanasia in the Low Countries or for medical assistance in suicide in Switzerland. Irrespective of the shape of the law, the fundamental challenge remains, to live well together despite the vicissitudes of life.
Keywords: assisted dying; Werther; Contagion; Media; Suicide; Suicide Prevention